Plasma IL-6 levels in unmedicated, comorbidity free obsessive-compulsive disorder. (2nd November 2021) - Jose, Dania; Dinakaran, Damodharan; Shivakumar, Venkataram; Subbanna, Manjula; Reddy, Y. C. Janardhan; Venkatasubramanian, Ganesan; Narayanaswamy, Janardhanan C.
Abstract: Background: Obsessive-compulsive disorder (OCD) is increasingly being evaluated for a neuro-immune basis. Interleukin-6 (IL-6) is the most widely studied cytokine with a potential role in altering neurotransmission. The evidence for plasma IL-6 alterations in OCD has yielded mixed results. Psychotropic medications are known to modulate inflammatory processes and cytokine levels. Methods: In this study, we recruited unmedicated, co-morbidity-free adult OCD patients ( n  = 49) and sex-matched healthy controls HC ( n  = 47) and compared their plasma IL-6 levels and their correlation with age at onset, duration of illness, and severity. Results: IL-6 plasma level (ng/ml) in unmedicated OCD patients (1.31 ± 0.67) was significantly greater compared to HC (1.03 ± 0.47) [ t  = 2.33 ( p  = 0.02)]. The group differences persisted even after controlling for age and sex [ F (1, 91) = 4.57, p  = 0.035, η 2 = 0.05]. Plasma IL-6 did not correlate significantly with any clinical variables. Conclusions: This study adds to the existing literature on immune alterations in OCD. Alterations in plasma IL-6 might have implications in the neurotransmitter alterations and stress-response in OCD. The current study results in unmedicated and comorbidity-free OCD patients give us a better understanding of the immune alterations in OCD. Future studies in such a population will probably help in reducing the heterogeneity of findings.